Prediction and Validation of Load-Dependent Behavior of the Tibiofemoral and Patellofemoral Joints During Movement - Lenhart, Rachel L. (Ann Biomed Eng, 2015)
The study objective was to construct and validate a subject-specific knee model that can simulate full six degree of freedom tibiofemoral and patellofemoral joint behavior in the context of full body movement. Segmented MR images were used to reconstruct the geometry of 14 ligament bundles and articular cartilage surfaces. The knee was incorporated into a lower extremity musculoskeletal model, which was then used to simulate laxity tests, passive knee flexion, active knee flexion, and human walking. Simulated passive and active knee kinematics were shown to be consistent with subject-specific measures obtained via dynamic MRI. Anterior tibial translation and internal tibial rotation exhibited the greatest variability when uncertainties in ligament properties were considered. When used to simulate walking, the model predicted knee kinematic patterns that differed substantially from passive joint behavior. Predictions of mean knee cartilage contact pressures during normal gait reached 6.2 and 2.8 MPa on the medial tibial plateau and patellar facets, respectively. Thus, the dynamic modeling framework can be used to simulate the interaction of soft tissue loads and cartilage contact during locomotion activities, and therefore provides a basis to simulate the effects of soft tissue injury and surgical treatment on functional knee mechanics.